1996
DOI: 10.1103/physrevb.53.13193
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Dominant density parameters and local pseudopotentials for simple metals

Abstract: Although the underlying all-electron calculations employed the correct local density approximation for exchange and correlation, the pseudopotential calculations for solids inadvertently used the local field correction for exchange alone. The corrected universal ͑U͒ and individual ͑I͒ pseudopotential parameters are given here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 0 publications
3
48
0
Order By: Relevance
“…is the average repulsive part of the pseudopotential and egS is the band-structure energy, given by: On the other hand, the interstitial density condition is: The mechanical properties calculated with the potential (1) turned out to be in very good agreement with experiment [3]. They are generally better than non-perturbative results with nonlocal pseudopotentials, probably due to the stability condition (2).…”
Section: Introductionsupporting
confidence: 55%
“…is the average repulsive part of the pseudopotential and egS is the band-structure energy, given by: On the other hand, the interstitial density condition is: The mechanical properties calculated with the potential (1) turned out to be in very good agreement with experiment [3]. They are generally better than non-perturbative results with nonlocal pseudopotentials, probably due to the stability condition (2).…”
Section: Introductionsupporting
confidence: 55%
“…Table I presents results for equilibrium bond lengths and binding energies per atom for the Na dimer and an octahedral Na 6 cluster calculated with three different approximations. All the calculations use the LDA for exchange and correlation, but differ in their treatment of the electron-ion 30 We see that the use of the pseudopotential overestimates the bond lengths by 2%-3%, but the increased bond length in Na 6 over that in the dimer is reproduced. The binding energies, with respect to spin-polarized free atoms, are also in reasonable agreement.…”
Section: ͑5͒mentioning
confidence: 83%
“…We use the Perdew and Zunger parametrization 28 of the electron gas results of Ceperley and Alder. 29 The external field contains the electron-ion interaction, V ext (r)ϭ ͚ i v(rϪR i ), where we take for v the local pseudopotential of Fiolhais et al, 30 which reproduces very well the properties of bulk sodium and has shown good transferability to sodium clusters. 31 Although some progress has been made recently for including the effects of nonlocality in the pseudopotential in orbital-free schemes, 32 these effects are expected to be small for sodium.…”
Section: A Car-parrinello Molecular Dynamics With Orbitalfree Energymentioning
confidence: 99%
“…The range of our pseudopotential increases with atomic number for the alkali elements. 26 We have performed a series of static calculations for the K 2 , Rb 2 and Cs 2 molecules in order to construct their binding energy curves, and have found that the range of the interatomic interaction increases together with the range of the pseudopotentials, so a decrease in the height of the specific heat peak is expected in the series Na→K→Rb→Cs. This is what is observed indeed.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 In the external field acting on the electrons, V ext ( r) = n v( r − R n ), we take v to be the local pseudopotential of Fiolhais et al, 26 which reproduces well the properties of bulk alkalis and has been shown to have good transferability to alkali clusters. 27 The cluster is placed in a unit cell of a cubic superlattice, and the set of plane waves periodic in the superlattice is used as a basis set to expand the valence density.…”
Section: Theorymentioning
confidence: 99%